Empowering futures: A financial literacy assessment among graduate students at Tribhuvan university - Lamichhane, Basu Dev; Bhaumik, Amiya; Gnawali, Achyut (International Journal of Business Strategy and Social Sciences, 2024)
The purpose of this study is to assess the level of financial literacy among graduate students. The focus is on exploring the relationship between financial literacy and three key factors: financial attitude, financial knowledge, and financial behavior. The study targeted graduate students at Tribhuvan University’s Faculty of Management (FOM) in Kathmandu valley with 710 students receiving a structured questionnaire. Total of 427 valid responses were received, establishing the sample for analysis. Descriptive and relational research designs was adopted for the analysis. Data was collected through a structured questionnaire, reflecting participants’ financial attitudes, knowledge, and behaviors. The study concludes that there exists a positive association between the levels of students’ financial attitudes, knowledge, and behaviors with their financial literacy. Additionally, the research findings reveal a significant and positive impact of financial attitude, knowledge, and behavior on financial literacy. Government authorities will utilize findings of the study for the development of policies aimed at enhancing financial literacy programs in Nepal. Banking and Financial Institutions (BFIs), Microfinance Institutions (MFIs) as well as regulators can use the insights to modify financial literacy programs that address the specific needs identified in the study. Professors, teachers, and trainers can incorporate with the study’s results for curriculum planning, designing courses to foster financial attitudes, knowledge, and behaviors among graduate and post-graduate students.